Effect of device-guided paced breathing of biofeedback on blood pressure, stress and anxiety levels in hypertensives (Research, Society and Development, 2021)
The present study aimed to evaluate the influence of cardiac coherence through Biofeedback Therapy (BT) with paced breathing on blood pressure, stress and anxiety levels in individuals with essential arterial hypertension. The participants underwent 8 sessions of paced breathing guided by biofeedback visual therapy   for 20 minutes, in which they were evaluated through clinical assessment, Hamilton Anxiety Rating Scale, Perceived Stress Scale and cardiovascular variables. Comparisons of means were performed using the paired and unpaired Student's t-test. Statistically significant correlations were considered when p ≤ 0.05 with a 95% confidence interval. The effect size (Cohen's d) and common language effect size were calculated to assess the effect of such therapy. Sixteen patients with mean age of 57.3 ± 14 years old participated in this study. Comparisons between mean initial and final systolic blood pressure levels (SBP) in women (p = 0.007; Cohen's d = 0.50), pre- and post-training heart rate (p = 0.02; Cohen's d = 0.60) and anxiety levels (p = 0.01; Cohen's d = 1.04) were significant. Comparisons between pre- and post-training SBP (p = 0.006; Cohen's d = 0.81) and pre- and post-training anxiety levels (p = 0.04; Cohen's d = 0.32) were significant among males. In conclusion, paced breathing training with biofeedback therapy can be promising to reduce anxiety levels in individuals with essential arterial hypertension.